ANALISIS STRATEGI KELUARGA DALAM MENANAMKAN PENDIDIKAN ISLAM SEBAGAI SOLUSI MENGATASI KRISIS MORAL ANAK DI ERA GLOBALISASI - Ananda Dwi Putri; Syifa Fauziah Ahmad; Putri Gita Lestari; Siti Khotijah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study examines the important role of families in instilling Islamic educational values ​​as an effort to overcome the moral crisis of children in the midst of the globalization era. The main objective of this study is to examine how the role of families through parenting patterns, role models, and instilling Islamic teachings can shape children's character so that they remain based on religious values ​​amidst the onslaught of foreign cultures and the development of digital technology. This study uses a library research method by analyzing various sources of literature, books, scientific articles, and relevant secondary data. The results of the study show that families have a central role as the first educational environment in building children's moral foundations, even though they are faced with challenges such as the influence of digital media and limited parental time. The conclusion of this study confirms that active family participation is essential in Islamic-based character education in order to produce a generation that is faithful and has commendable morals.